Travel Back in Time: Design Methods of Two Billionaire Industrialists - Grudin, Jonathan (ACM Interactions, 2008)
In this column we take a break from HCI history to revisit two earlier 20th-century technology successes. Rather than moving bits, these were people-movers. Early in the century, Henry Ford revolutionized the design, manufacture, and use of automobiles. Subsequently, Howard Hughes revolutionized the design and use of aircraft. Each was a self-taught engineer who created an industry that changed the world.